Advances in reproductive management strategies for thyroid cancer patients during the perinatal period: a narrative review - Dong, Ying; Gou, Juxiang (Frontiers in Oncology, 2025)
Changes in thyroid function during the perinatal period significantly impact patients’ fertility, necessitating targeted adjustments in management strategies to ensure hormone stability while weighing the effects of treatment on both the mother and the fetus. Therefore, comprehensive management during the perinatal period is essential to promote effective reproductive outcomes. This study aims to review the relationship between thyroid cancer and fertility, focusing on reproductive management strategies during the preconception, pregnancy, and postpartum periods in patients with thyroid cancer. Additionally, we will synthesize this information into illustrative figures to provide clinical healthcare professionals with a theoretical foundation for improving reproductive care for thyroid cancer patients throughout the perinatal period, thereby facilitating comprehensive reproductive health management.